2019
DOI: 10.1002/admi.201900195
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self‐Assembly and Organization of Collagen at Solid/Liquid Interface: Effect of Spheroid‐ and Rod‐Shaped TiO2 Nanocrystals

Abstract: The adsorption behavior of collagen on solid surfaces is a process that determines the role of this protein to mediate cell–material interaction. Herein, the mechanism of self‐assembly and organization of collagen on a model substrate is investigated in the presence of TiO2 nanoparticles. In solution, results show that nanoparticles do not alter the conformation of collagen (triple‐helix), and slightly delay the kinetics of its self‐assembly. In the adsorbed state, by exploring the dewetting patterns of collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…However, the recorded images did not allow the structure of individual fibrils, particularly their D-periodicity, to be sufficiently resolved. This may be due to their mobility during imaging, resulting on their interaction with the AFM tip, as commonly observed on adsorbed collagen layers [21] and collagen-based tissues [22]. In the dried phase (Figure 4C,D), the organization of these fibrils showed an alignment similar to that observed in the hydrated state, even if some disrupted fibrils could be observed (see arrow in Figure 4C).…”
Section: Preserved Morphological Characteristics Of Capsules and Cell...mentioning
confidence: 60%
“…However, the recorded images did not allow the structure of individual fibrils, particularly their D-periodicity, to be sufficiently resolved. This may be due to their mobility during imaging, resulting on their interaction with the AFM tip, as commonly observed on adsorbed collagen layers [21] and collagen-based tissues [22]. In the dried phase (Figure 4C,D), the organization of these fibrils showed an alignment similar to that observed in the hydrated state, even if some disrupted fibrils could be observed (see arrow in Figure 4C).…”
Section: Preserved Morphological Characteristics Of Capsules and Cell...mentioning
confidence: 60%
“…Indeed, when collagen molecules (triple-helix) adsorb onto solid surfaces, it has been shown that they adopt a conformation that favors their self-assembly into fibrillary nanostructures and, in many situations near physiological conditions, they interact with the surface through few residues while segments protrude in the solution. 54,55 Besides, the formation of fibrils has also been observed even when collagen is embedded in polyelectrolyte multilayers. 38 In the present study, AFM images recorded on (Col/HA) 3 multilayers, after cross-linking, show the presence of well-defined fibrils (Figure 7A), which becomes invisible after the subsequent deposition of (PAH/ALP) 5 multilayers (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…The sensors were cleaned by UV-ozone for 15 min and rinsed with ethanol before measurement. Oscillation of the quartz crystal at the resonant frequency (5 MHz) or at one of its overtones (15,25,35,45,55, and 65 MHz) was obtained by applying an ac voltage. The evolution of the resonance frequency (Δf) and of dissipation (ΔD) was monitored upon adsorption of the different components.…”
Section: Mineralization In Solutionmentioning
confidence: 99%
“…While these studies demonstrate the promising potential of combining collagen and NPs, it is obvious that there is a lack of a comprehensive understanding regarding the mechanism by which NPs interact with collagen in aqueous solutions of biological interest. This issue remains elusive, and only a few papers have reported the impact of NPs on the self-assembly of collagen in solution or at the solid/liquid interface . By contrast, it has been the subject of a vast literature for various proteins and led, for the instance, to the emergence of the protein corona , and surface-assisted fibrillation , paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…This issue remains elusive, and only a few papers have reported the impact of NPs on the self-assembly of collagen in solution 32 or at the solid/ liquid interface. 35 By contrast, it has been the subject of a vast literature for various proteins and led, for the instance, to the emergence of the protein corona 36,37 and surface-assisted fibrillation 38,39 paradigms.…”
Section: Introductionmentioning
confidence: 99%